The stimulative effects of intergovernmental grants and the marginal cost of public funds - Bev Dahlby; Ergete Ferede (Center for Economic Studies and ifo Institute (CESifo), 2012)
We test the hypothesis that the flypaper effect can arise if the recipient government finances part of its expenditures with a distortionary tax. We present a simple theoretical framework that shows how a lump-sum transfer stimulates the marginal expenditures of a recipient government through an income effect and a price effect. We test the predictions of this model using data on Canadian provincial expenditures and federal transfers to the provinces over the period 1981 to 2008. Our econometric results indicate that a 0.10 increase in a provincial government's marginal cost of public funds increases the stimulative effect of lump-sum grants by 0.32.
Keywords: H72; H77; 330; intergovernmental grants; marginal cost of public funds; flypaper effect; Flypaper-Effekt; Finanzausgleich; Öffentliche Ausgaben; Schätzung; Kanada